2014
DOI: 10.1186/s12896-014-0102-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of anode and anolyte community growth and the impact of impedance in a microbial fuel cell

Abstract: BackgroundA laboratory-scale two-chamber microbial fuel cell employing an aerated cathode with no catalyst was inoculated with mixed inoculum and acetate as the carbon source.Electrochemical impedance spectroscopy (EIS) was used to study the behavior of the MFC during initial biofilm (week 1) and maximum power density (week 20). EIS were performed on the anode chamber, biofilm (without anolyte) and anolyte (without biofilm). Nyquist plots of the EIS data were fitted with two equivalent electrical circuits to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…The main phylum that was enriched on the anode after 30 days of stable operation in MFC was Bacteroidetes, which increased from 0.8% in the inoculum to 34% in the MFC (Figure 3). Bacteroidetes have previously been reported to dominate the anode consortium of a two-chamber MFC fed wheat straw hydrolysate, and were also found in two-chamber acetate-fed MFCs [16,32] as well as in a single-chamber MFC [33]. The most abundant phylum was Firmicutes, with 32% in the inoculum and 50% after 30 days.…”
Section: Microbial Community Analysismentioning
confidence: 89%
“…The main phylum that was enriched on the anode after 30 days of stable operation in MFC was Bacteroidetes, which increased from 0.8% in the inoculum to 34% in the MFC (Figure 3). Bacteroidetes have previously been reported to dominate the anode consortium of a two-chamber MFC fed wheat straw hydrolysate, and were also found in two-chamber acetate-fed MFCs [16,32] as well as in a single-chamber MFC [33]. The most abundant phylum was Firmicutes, with 32% in the inoculum and 50% after 30 days.…”
Section: Microbial Community Analysismentioning
confidence: 89%
“…Indeed, polarization curves are generally used to measure the open circuit voltage (OCV) and to estimate both the maximum current density and the maximum power output of the MFCs (Clauwaert et al, 2008). Instead, EIS is a powerful AC technique widely employed in different fields of electrochemistry (Barsoukov & Macdonald, 2005;Hernández et al, 2014;Hernández et al, 2015), including MFC systems (Dominguez-Benetton et al, 2012;Martin et al, 2013;Sanchez-Herrera et al, 2014), which results highly useful when the different resistances values for each process involved in the MFC operation cannot be easily determined from a polarization curve. EIS is considered as an accurate technique for analyzing bio-electrochemical reactions on electrodes, internal resistances, biofilm development and immobilization on the different materials, estimating electrode properties, and studying the mass transfer resistances due to the diffusion limitations of the reactants (Dominguez-Benetton et al, 2012;He & Mansfeld, 2009;Manohar et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This is due to differences in anode biofilm. It has been reported that microbial growth has a beneficial effect on anode biolectrochemical kinetics, causing changes in charge transfer resistance, as a previous work observed that charge transfer resistance decreased from 7427 to 55.73 Ω between 1 and 20 weeks, which was attributed to anode microbial density increase …”
Section: Resultsmentioning
confidence: 62%
“…It has been reported that microbial growth has a beneficial effect on anode biolectrochemical kinetics, causing changes in charge transfer resistance, as a previous work observed that charge transfer resistance decreased from 7427 to 55.73 Ω between 1 and 20 weeks, which was attributed to anode microbial density increase. 81 The coefficient of constant phase element > 0.80, as was the case with the Nafion ® stack, AMI-7001 stack and CMI-7000 stack, suggests a pseudocapacitive process in the anode electrode. It has been demonstrated through impedance measurements that the carbon veil and anode biofilm, in an MFC, are capable of storing energy, obtaining coefficient values up to 0.89 and 0.78 for carbon veil and biofilm, respectively, 82 demonstrating that carbonaceous materials such as biofilm have pseudocapacitive behavior.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 86%